Are repetitive pericranial nerve blocks effective in the management of chronic paroxysmal hemicrania?: A case report. Issue 31 (August 2019) - Ertem, Devrimsel Harika
Abstract: Introduction: Paroxysmal hemicrania (PH) is a chronic headache disorder characterized by unilateral pain attacks accompanied by cranial autonomic symptoms and responds to indomethacin completely. There are few alternative treatment options for the patients who cannot tolerate indomethacin. Studies exploring the effects of repetitive peripheral cranial nerve blocks in the management of chronic PH are limited. Patient concerns and diagnosis: A 34-year-old woman with a 4-year history of PH was evaluated. Her pain was prevented by indomethacin without side effects; however, she wanted to try to conceive. Interventions: Repetitive pericranial nerve blocks, great occipital nerve, infraorbital nerve, supraorbital nerve, and sphenopalatine ganglion block, using local anesthetics and steroids were performed once a week for a 6 weeks period. Outcomes: A follow-up of 3 months showed that there was no pain relief following the injections and patient was needed to be maintained on indomethacin. Conclusion: Although pericranial nerve blocks have been tried in chronic PH cases with positive influences, this case indicated that repetitive nerve blocks were not always a successful therapy option.